EFEKTIVITAS ACTIVE CYCLE OF BREATHING TECHNIQUE (ACBT)TERHADAP PENINGKATAN KAPASITAS FUNGSIONAL PADA PASIEN BRONKIEKTASIS POST TUBERKULOSIS PARU - Pratama, Aditya Denny (UI Scholars Hub, 2021)
Bronchiectasis is a chronic disorder characterized by irreversible bronchial dilatation accompanied by an inflammatory process in the walls of the bronchi and the surrounding lung parenchyma. Bronchiectasis can be caused by infection with the bacterium Mycobacterium Tuberculosis which is the bacteria that causes pulmonary tuberculosis (pulmonary TB). The main characteristic of bronchiectasis is the accumulation of mucus, chronic bacterial infections, and persistent bronchial inflammation. The purpose of this case study was to determine the effectiveness of the Active Cycle Of Breathing Technique (ACBT) on increasing functional capacity in bronchiectasis patients with pulmonary tuberculosis. The research method used is in the form of a case report with 1 patient given physiotherapy intervention and evaluation 4 times. To overcome some of the problems that arise, namely shortness of breath, and sputum retention due to bronchiectasis after pulmonary tuberculosis in this study, physiotherapy interventions were used, namely exercise therapy in the form of ACBT. The results obtained after 4 times of therapy were a decrease in tightness as evidenced by the Borg scale from 4 to 1, and a reduction in sputum retention with the auscultation results in the form of rhonchi in the posterior apical segment of the bilateral upper lobe to rhonchi in the posterior apical segment of the right upper lobe. Based on these results, it can be concluded that physiotherapy interventions with ACBT effectives in patients with post pulmonary tuberculosis bronchiectasis.